Cardiocerebral infarction - Stojanović, Jelena (Halo 194 Scientific Journal of Emergency Medicine, 2021)
Introduction / Objective  We present as a priority CCI detected at the prehospital level.Case report: The case of a 78-year-old woman with the simultaneous development of AMI and AIMU is presented. In prehospital conditions, the suspicion of cardiocerebral infarction was established on the basis of heteroanamnestic data, clinical picture and ST-elevation on the electrocardiogram. In the competent health institution, both diagnoses were confirmed on the basis of MDCT of the endocranium, ultrasound examination of the heart and elevated troponin values. Fibrinolytic therapy was applied, however, cardiac arrest developed. The applied KPR measures did not give an adequate response and a lethal outcome was stated.Conclusion: In the near future, a national guide on the diagnosis and treatment of this emergency should be developed, and until then, the best individual approach is for each patient.
Keywords: acute myocardial infarction, acute stroke, CCI